2018
DOI: 10.1063/1.5018714
|View full text |Cite
|
Sign up to set email alerts
|

Inertial migrations of cylindrical particles in rectangular microchannels: Variations of equilibrium positions and equivalent diameters

Abstract: Inertial migration has emerged as an efficient tool for manipulating both biological and engineered particles that commonly exist with non-spherical shapes in microfluidic devices. There have been numerous studies on the inertial migration of spherical particles, whereas the non-spherical particles are still largely unexplored. Here, we conduct three-dimensional direct numerical simulations to study the inertial migration of rigid cylindrical particles in rectangular microchannels with different width/height r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…† Our results with Escherichia coli (∼1 μm long) were in agreement with previous studies, where elongated particles have been reported to focus as spherical particles with an equivalent diameter approximately similar to the largest dimension. 37,38 Salmonella typhimurium (∼1-1.5 μm long) was thus expected to behave as larger particles than Escherichia coli since they were observed to be a bit longer. However, they behaved as particles slightly smaller than the equivalent for Escherichia coli; Fig.…”
Section: Demonstration With Bacteriamentioning
confidence: 99%
“…† Our results with Escherichia coli (∼1 μm long) were in agreement with previous studies, where elongated particles have been reported to focus as spherical particles with an equivalent diameter approximately similar to the largest dimension. 37,38 Salmonella typhimurium (∼1-1.5 μm long) was thus expected to behave as larger particles than Escherichia coli since they were observed to be a bit longer. However, they behaved as particles slightly smaller than the equivalent for Escherichia coli; Fig.…”
Section: Demonstration With Bacteriamentioning
confidence: 99%
“…For cylindrical particles flowing in a square channel as well, Su et al [ 45 ] demonstrated numerically that there are always four stable equilibrium positions for Re varying from 50 to 200. The two-stage process (cross-streamline and cross-lateral migrations) was also shown for these cylindrical particles.…”
Section: Rotational and Migratory Behaviors Of A Particle Flowing mentioning
confidence: 99%
“…Unlike spherical particles [ 16 , 60 ], non-spherical ones oscillate while being transported in a microchannel flow. Hur et al [ 55 ], Masaeli et al [ 49 ], and Su et al [ 45 ] observed that an elongated particle ( λ > 1) will keep oscillating regardless of its position in the channel (still migrating or focused on an equilibrium position) ( Figure 11 ). This might be due to the fact that a prolate particle prefers to tumble (see Section 2.1.3 ) and that, while adopting this type of rotation, the angular velocity, the sweeping area, and the distance from the wall continuously change, leading to periodical variations of the wall-induced lift force and thus a periodic motion of the particle toward and away from the wall [ 45 ].…”
Section: Rotational and Migratory Behaviors Of A Particle Flowing mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the aforementioned designs mainly depend on experience. The particle's detailed motion in microchannels remains unclear, though a large body of research has been devoted to particles’ motions suspended in liquid ( Lu et al, 2017b , Su et al, 2018 , Zhang et al, 2016 ) instead of air. In a straight liquid microchannel, initial randomly distributed neutrally buoyant particles will finally migrate to several symmetric equilibrium positions due to the inertial effect ( Liu et al, 2015 , Martel and Toner, 2014 , Zhang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%